Elevation differences, composited images, and lines of narrow-steep slopes/headwalls of retrogressive thaw slumps data derived from ArcticDEM (Release 7), pan-Arctic (2008-2017) - Lingcao Huang (Arctic Data Center)
Data are available for download at http://arcticdata.io/data/10.18739/A2ZS2KF4B Data products derived from ArcticDEM (Release 7) for the pan-Arctic at a resolution of 2 meters. These products include elevation differences, composited images, and lines of narrow-steep slopes/headwalls of retrogressive thaw slumps. The elevation differences represent changes in topography by comparing the most recent Digital Elevation Model (DEM) and the oldest one available at each location. Composited images are the hillshades derived from the newest DEM files in the background and lines of narrow-steep slopes on the top. Lines of narrow-steep changes represent locations where slopes change abruptly, and those showing patterns of the movement of a thaw slump are saved into a separate file.